Introduction: Document/ation : Pouvoir, intérêts, redevabilités - Pigg, Stacy Leigh; Erikson, Susan L.; Inglis, Kathleen (Anthropologica, 2018)
In this introduction we argue that ethnographic attention to documents, as a mundane feature of everyday life, can reveal social manoeuvres that accelerate or detain particular configurations of power and accountability. We use the term “document/ation” to convey this space of possibility in moments of action. The articles collected in this special issue foreground the dynamic tensions between systematisation and ambiguity that arise in situations of verification, appraisal or validation.